Can the BestGrid Process Improve Stakeholder Involvement in Electricity Transmission Projects? - Nadejda Komendantova; Marco Vocciante; Antonella Battaglini (Energies, 2015)
The European Union has set ambitious targets for deployment of renewable energy sources to reach goals of climate change mitigation and energy security policies. However, the current state of electricity transmission infrastructure is a major bottleneck for further scaling up of renewable energy in the EU. Several thousands of kilometers of new lines have to be constructed and upgraded to accommodate growing volumes of intermittent renewable electricity. In many countries, construction of electricity transmission projects has been delayed for several years due to concerns of local stakeholders. The innovative BESTGRID approach, reported here, brings together transmission system operators (TSOs) and non-governmental organizations (NGOs) to discuss and understand the nature of stakeholder concerns. This paper has three objectives: (1) to understand stakeholder concerns about the deployment of electricity transmission grids in four pilot projects according to five guiding principles: need, transparency, engagement, environment, and impacts on human health as well as benefits; (2) to understand how these principles can be addressed to provide a basis for better decision-making outcomes; and (3) to evaluate the BESTGRID process based on feedback received from stakeholders and the level of participation achieved according to the ladder of Arnstein. This paper goes beyond a discussion of “measures to mitigate opposition” to understand how dialogue between TSOs and the public—represented mainly by NGOs and policy-makers—might lead to a better decision-making process and more sustainable electricity transmission infrastructure deployment.